A revision of Festuca (Poaceae: Loliinae) in South American paramos - Stancik, Daniel; Peterson, Paul M. (Washington, D. C. : Smithsonian Institution Scholarly Press, 2007)
Stancik, Daniel and Paul M. Peterson. A revision of Festuca (Poaceae: Loliinae) in South American paramos. Smithsonian Contributions from the United States National Herbarium, Volume 56, 184 pages (including 97 fi gures). A taxonomic revision of Festuca L. for the South American paramos of Brazil, Colombia, Ecuador, northern Peru, and Venezuela is given. Fifty-six species and six subspecies of Festuca are recognized in the study area. Fifty-three species are native to the fl ora region and three are introduced and cultivated. Keys for determining the species, a classifi cation, synonymies, descriptions, leaf anatomical descriptions, observations, distribution and habitat, specimens examined, illustrations, and leaf surface micrographs are provided. One species: F. turimiquirensis Stancik & P.M. Peterson, and one subspecies: F. tolucensis subsp. culata Stancik & P.M. Peterson, are newly described. The following three names were lectotypifi ed: Bromus caldasii Kunth [=Festuca caldasii (Kunth) Kunth], Festuca fratercula Rupr. ex E. Fourn. (=Festuca amplissima Rupr. subsp. amplissima), and Festuca ovina subvar. jamesonii St.-Yves (=Festuca glumosa Hack. ex E.B. Alexeev)
Contributions from the United States National Herbarium volume 56.
Includes bibliographical references and index.
Summary in Spanish.
Keywords: Fescue -- South America